Pengaruh Motivasi Kerja, Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Negeri Sipil Pada Saat Pandemi Covid 19 Di Kecamatan Gunung Agung - Japlani, Ardiansyah; Suryadi, Suryadi; Lianti, Novi (Universitas Muhammadiyah Metro, 2023)
The basic problem is the lack of human qualities that can hinder the growth anddevelopment of the national economy. Lack of humanity will also be a stumbling block in theera of globalization, because the era of globalization is a time of quality competition. If theIndonesian people want to participate in the global stage, then the first step is that whatneeds to be done is to organize their personality, both mentally, spiritually, creatively,morally and responsibly. the quality of human resources related to performance. This studyaims to determine 1) To find out whether the motivation variable has an effect on employeeperformance. 2) To find out whether the variable of Leadership on Employee Performance.3) To find out whether the work environment variable on employee performance. 4) Todetermine the effect of the variables of Motivation, Leadership, Work Environment, togetheron Employee Performance. The survey method was chosen as the primary data source. Thesurvey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using aquestionnaire or questionnaire instrument. In this study, the population is consumers whouse telkom products. The sampling technique uses accidental sampling. The population inthis study are all employees who work at the Gunung Agung sub-district office, namely 57employees and temporary employees. The results showed that 1) there was a positive andsignificant influence between motivation on employee performance 2) there was a positiveand significant influence between leadership on employee performance. 3) there is apositive and significant influence between the work environment on employee performance.4) there is a positive and significant influence between motivation, leadership and workenvironment on employee performance